A STAB IN THE FORBIDDEN TERRITORY - Tariq, Khuzaima; Asmat Achakzai; Muneer Amanullah; Asad Awan (Journal of Ayub Medical College Abbottabad, 2022)
Penetrating heart injuries are associated with higher mortality rates. Coronary lesions caused by penetrating trauma are considered even rarer and universally fatal. We present a case of a fortunate survivor who had complete transection of left anterior descending (LAD) artery with right ventricular (RV) tear after being stabbed by knife, arriving in emergency unit with massively bleeding chest wound. Complex cardiac trauma involving coronaries and cardiac chambers is a challenge to surgeons if patients miraculously reach the hospital alive. This patient had complete transection of LAD artery with penetration into RV cavity, he was successfully managed by timely and prompt surgical intervention by on call team. This case highlights the importance of team dynamics working in harmony during emergency situations, we stress upon conducting routine drills to train surgical residents, perfusionists and operation theatre staff.